Prognostic Significance of Nuclear Phospho-ATM Expression in Melanoma. - Madhuri Bhandaru; Magdalena Martinka; Kevin J McElwee; Anand Rotte (PLoS ONE, 2015)
UV radiation induced genomic instability is one of the leading causes for melanoma. Phosphorylation of Ataxia Telangiectasia Mutated (ATM) is one of the initial events that follow DNA damage. Phospho-ATM (p-ATM) plays a key role in the activation of DNA repair and several oncogenic pathways as well as in the maintenance of genomic integrity. The present study was therefore performed to understand the significance of p-ATM in melanoma progression and to correlate it with patient prognosis. Tissue microarray and immunohistochemical analysis were employed to study the expression of p-ATM in melanoma patients. A total of 366 melanoma patients (230 primary melanoma and 136 metastatic melanoma) were used for the study. Chi-square test, Kaplan-Meier, univariate and multivariate Cox regression analysis were used to elucidate the prognostic significance of p-ATM expression. Results revealed that both loss of, and gain in, p-ATM expression were associated with progression of melanoma from normal nevi to metastatic melanoma. Patients whose samples showed negative or strong p-ATM staining had significantly worse 5-year survival compared to patients who had weak to moderate expression. Loss of p-ATM expression was associated with relatively better 5-year survival, but the corresponding 10-year survival curve almost overlapped with that of strong p-ATM expression. p-ATM expression was found to be an independent prognostic factor for 5-year but not for 10-year patient survival. In conclusion our findings show that loss of p-ATM expression and gain-in p-ATM expression are indicators of worse melanoma patient survival.